Tender savage - Johansen, Iris (New York Bantam Books, 2010)
A woman caught up in another country's revolution finds herself falling in love with a charismatic freedom fighter
13
Keywords: Man-woman relationships -- Fiction; Revolutions -- Fiction; Caribbean Area -- Fiction